Comparative effectiveness of antiplatelet therapy of hemostatic disorders in diabetes of the second type - S. A. Pavlishcuk; A. V. Romash (Кубанский научный медицинский вестник, 2015)
Presents a literature review on the effectiveness of antiplatelet prophylaxis of micro- and macroangiopathies in diabetes mellitus type 2.